The Role of Physical Activity in Successful Aging and Its Impact on Health and Life Satisfaction in Seniors - Wolff, Anna; Rosińska-Lewandoska , Dominika; Lewandowska, Dominika; Udziela-Gil, Helena; Szewczyk, Marcelina; Ufnal, Julia; Morawska, Maria; Gruszka, Szymon; Bryła, Karolina; Jarosz, Kinga (Journal of Education, Health and Sport, 2025)
Demographic aging of populations is a phenomenon observed in most countries worldwide. As a result, extending healthy life has become one of the key objectives of health policies in many nations. The World Health Organization (WHO) has developed a definition of healthy aging, describing it as the process of developing and maintaining functional abilities that ensure well-being in older age. In addition to systemic solutions supporting seniors, physical activity plays a critical role in the process of healthy aging. It is fundamental for maintaining physical fitness and independence in older adults. This paper aims to discuss the role of physical activity in the process of successful aging, reducing the risks associated with comorbidities, and its positive impact on overall life satisfaction.